2019
DOI: 10.1016/j.isci.2019.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics Analyses of HNF4α Protein Domain Function during Human Pluripotent Stem Cell Differentiation

Abstract: During mammalian development, liver differentiation is driven by signals that converge on multiple transcription factor networks. The hepatocyte nuclear factor signaling network is known to be essential for hepatocyte specification and maintenance. In this study, we have generated deletion and point mutants of hepatocyte nuclear factor-4alpha (HNF4a) to precisely evaluate the function of protein domains during hepatocyte specification from human pluripotent stem cells. We demonstrate that nuclear HNF4a is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…From these images, we noted that the HNF4a western blot showed the presence of 2 bands in mouse liver extracts. The lower band corresponded to the predicted molecular weight of mouse HNF4a ($53 kDa), and the upper band corresponded to SUMO2-modified HNF4a described recently in human hepatocytes (Wang et al, 2019;Zhou et al, 2012). Statistical analysis of each of these bands between the four treatment groups showed that the lower band was significantly increased only by acute fasting, consistent with our proteomics dataset, but the upper band showed a statistically significant decrease in livers of animals harvested in the fasted state from either diet group ( Figure 6C).…”
Section: Hnf4a Is Regulated By Eodf To Modulate Transcriptionmentioning
confidence: 54%
“…From these images, we noted that the HNF4a western blot showed the presence of 2 bands in mouse liver extracts. The lower band corresponded to the predicted molecular weight of mouse HNF4a ($53 kDa), and the upper band corresponded to SUMO2-modified HNF4a described recently in human hepatocytes (Wang et al, 2019;Zhou et al, 2012). Statistical analysis of each of these bands between the four treatment groups showed that the lower band was significantly increased only by acute fasting, consistent with our proteomics dataset, but the upper band showed a statistically significant decrease in livers of animals harvested in the fasted state from either diet group ( Figure 6C).…”
Section: Hnf4a Is Regulated By Eodf To Modulate Transcriptionmentioning
confidence: 54%
“…One common problem is too low expression of hepatocyte-specific genes; a further challenge is expression of 'unwanted genes' that are not observed in primary human hepatocytes (Sachinidis et al 2019;Godoy et al 2015). The present systematic study of Wang et al (2019) showed that HNF4α does not only play a role in the steps of final differentiation from hepatoblasts to mature hepatocytes but also during development from endoderm to hepatoblasts.…”
mentioning
confidence: 61%
“…It contains several functional regions, the N-terminal transactivation domain (AD-1), a zinc finger DNA-binding domain, a flexible hinge region, a multifunctional ligand-binding domain with a second transactivation domain (AD-2), and a repression region (Lau et al 2018;Dhe-Paganon et al 2002). In the present study, Wang et al used CRISPR-Cas 9 genome-editing techniques to understand the role of the DNA-binding domain and the transactivation domains (AD-2) during differentiation of stem cells to hepatocyte-like cells (Wang et al 2019). Interestingly, the two modifications had a different influence on stem-cell specification.…”
mentioning
confidence: 91%
See 2 more Smart Citations